Introduction to International business - Pham, Huong Trang (Khoa Quốc tế, ĐHQGHN, 2020)
This introductory course provides a clear introduction and understanding of International business such as principles of international business, risks and challenges to face, issues in making decisions such as contexts and choice of market, ethics and CSR.